Epidemiologic profile, clinical and maternal mortality ratio in northeastern Brazil between 2010 and 2019: an ecologic study (Research, Society and Development, 2022)
Objective: to describe the epidemiological, clinical profile and maternal mortality ratio in the Northeast between 2010 and 2019. Methods: ecological, descriptive study, with data from the Mortality Information System (SIM) and Information System on Live Births (SINASC). The variables of the epidemiological profile refer to age, color/race, schooling and marital status, while the clinical variables deal with the place of occurrence, type of death due to obstetric cause, pregnancy period and investigation of death. A descriptive time series is also presented regarding the maternal mortality ratio in the period. Results: There were 4,521 maternal deaths in the period, of which 1,144 (25.30%) were recorded in Bahia. The epidemiological profile shows that the records refer to women between 25 and 34 years (42.68%), brown (66.95%), with 8 to 11 years of schooling (30.28%) and single (46.25%). Regarding clinical characteristics, 4057 (89.75%) of the deaths occurred in the hospital environment, 3141 (69.49%) for direct causes and 2800 (61.93%) during the puerperium. In 2013, the highest maternal mortality ratio was observed, with 61 deaths per 100,000 live births, in contrast to 2019, with 47 deaths per 100,000 live births. Conclusion: It was possible to elucidate the epidemiological and clinical profile of maternal deaths in the Northeast between 2010 and 2019. Furthermore, the variation in the maternal mortality ratio observed over the years is a relevant fact, but it should be analyzed in the light of analytical studies that explore the trend, especially in a region historically neglected in terms of socioeconomic development and access to health.